14 years of 6.7 GHz periodic methanol maser observations towards G188.95+0.89. Issue Volume 15:Issue S356(2019) (October 2019) - Mutie, Martin M.; Baki, Paul; Chibueze, James O.; El Bouchefry, Khadija
Abstract: We report the results of 14 years of monitoring of G188.95+0.89 periodic 6.7 GHz methanol masers using the Hartebeesthoek 26-m radio telescope. G188.95+0.89 (S252, AFGL5180) is a radio-quiet methanol maser site that is often interpreted as precursors of ultra-compact HII regions or massive protostar sites. At least five bright spectral components were identified. The maser feature at 11.36 km s -1 was found to experience an exponential decay during the monitoring period. The millimetre continuum reveals two cores associated with the source.